SPIRITUALITAS DALAM MUHAMMADIYAH - Iu Rusliana (Syifa al-Qulub, 2016)
Actually, Muhammadiyah is not anti-spirituality and sufism. However, its founder, KH Ahmad Dahlan like to use the term akhlaq despite sufism. It is caused that for him, sufism did not originate from the Quran and the Prophetic Tradition. Beside that, sufism is also identical with the implementation of religious teaching based on the guides of sufis and mursyids that are nearer to the superstitions, heresies and myths. Essencially, according to Mukti Ali, Muhammadiyah has implemented what is called sufism in the form of high social akhlaq. Theoritically, the spirituality of Muhammadiyah is nearer to modern sufism of Buya Hamka.